Transition to a Rural Green Economy with Eco-Agro Tourism: The Case of Kızıklı Aromatic Village (Türkiye) - ÖZGÜREL, Gizem; ATIŞ, Evren; ÇELİK UĞUZ, Sabriye (Journal of the Human and Social Sciences Researchers, 2023)
In the 21st century, where urban life and urban population continue to increase, the longing for green and the desire to return to nature attract people to destinations where nature-based activities is carried out. Eco-agro tourism, which is a type of tourism where eco-tourism and agro-tourism intersect, creates positive effects on the socio-cultural, economic and natural environment. Similarly, in the green economy approach, attention is drawn to the positive effects it creates in terms of economic welfare, quality of life and environmental protection. In addition, today the idea of destinations developing an economy based on environmentally friendly production is increasingly important. The study focused on eco-agro tourism, where the natural environment is placed at the center of the economic system in developing rural areas and sustainability in production and consumption can be achieved. It is thought that it is important to reveal the eco-agro tourism potential of the countryside from the perspective of the local people who know the region best. In addition, local people's ideas on eco-agro tourism for a sustainable "green economy" and "green-oriented development" should be known as it will show both the support they will give to tourism development and their participation in tourism activities. From this point of view, Kızıklı Village, which is connected to the Burhaniye district of Balıkesir, was chosen as the research sample. In the study, in which the qualitative research method was adopted, data were collected from 42 participants. The obtained data were subjected to content analysis, thematic groupings were made and their frequencies and percentages were presented to the reader. According to the data obtained from the field; it has been determined that Kızıklı village has eco-agro tourism potential, that the residents of the village will support eco-agro tourism development at a high level, and that eco-agro tourism can be the locomotive in strengthening the existing economic environment and making the green economy applicable in Kızıklı. Among the other results obtained from the research are that eco-agro tourism development and sustainability will be supported by the local people due to their positive contributions to the economic, natural and socio-cultural environment and that the local people will assume responsibilities as stakeholders.
Keywords: Turizm; Green Economy; Eco-Agro; Tourism; Aromatic Village; Sustainabilty; Sustainabilty; Eco-Agro; Yeşil Ekonomi; Eco-Agro; Turizm; Aromatik Köy; Sürdürülebilirlik; Tourism; Aromatic Village; Doğal Kaynaklar Ekonomisi; Sürdürülebilirlik; Green Economy; Yeşil Ekonomi; Green Economy; Eco-Agro; Tourism; Aromatic Village; Kızıklı Village; Natural Resources Economy; Aromatik Köy; 2. Zero hunger; 9. Industry and infrastructure; 1. No poverty; 15. Life on land; 16. Peace & justice; 7. Clean energy; 12. Responsible consumption; 13. Climate action; 8. Economic growth; 11. Sustainability